2020
DOI: 10.1177/0022034520976541
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Disparities in Dental Caries among Adolescents in China

Abstract: Comprehensive research on ethnic disparities in dental caries in China is limited. The aims of this cross-sectional study were to compare the levels of dental caries in adolescents between the Han ethnic group and ethnic minority groups in China and to explore the risk indicators for dental caries within ethnic subgroups. Data from the Fourth National Oral Health Survey in 2015, which covered all 31 province-level administrative divisions in mainland China, were used. The dental caries status in the permanent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…To achieve the goal that the prevalence of dental caries among 12-year-old children reducing to 30% by 2030, it is essential to invest in more resources to expand the coverage of the school-based oral health intervention programme and to allow the use of medical insurance accounts for dental preventive car e[ 43 ].. It is very likely that these proposed measures would reduce the inequality in the dental caries prevalence among Chinese school children and particularly benefit those living in the southwest and northeast regions [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…To achieve the goal that the prevalence of dental caries among 12-year-old children reducing to 30% by 2030, it is essential to invest in more resources to expand the coverage of the school-based oral health intervention programme and to allow the use of medical insurance accounts for dental preventive car e[ 43 ].. It is very likely that these proposed measures would reduce the inequality in the dental caries prevalence among Chinese school children and particularly benefit those living in the southwest and northeast regions [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…To ensure intra-examiner reliability of oral examination, 5% of samples were selected for duplicate examination, then compared with the original data and with the calibrating examiner every day during the survey. Cohen’s kappa statistics assessing the consistency of inter- and intra-examiner were all exceeded 0.80 [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Genetic factors that may influence susceptibility to dental caries, pulpitis and development of periapical granulomas and periodontal inflammation are not fully understood (Nibali et al, 2017). Wu et al (2021) reported ethnic disparities in dental caries among adolescents in China even after propensity score matching. In periodontal disease, genetic and epigenetic factors have been reported to determine susceptibility to inflammation in periodontal tissue, emphasizing the importance of immune homeostasis (Loos & Van Dyke, 2020).…”
Section: Introductionmentioning
confidence: 99%